Sport w sztuce. Sport in Art. 2012. Eds. M. KozioŁ, D. Piekarska, M. A. Potocka - Mazurkiewicz, Michał (Respectus Philologicus, 2013)
Sport w sztuce. Sport in Art. M. Kozioł, D. Piekarska, M. A. Potocka, eds. 2012. Kraków: Museum of Contemporary Art in Kraków. 200 pp. ISBN 978-83-62435-64-7. Sport in Art, published by the Museum of Contemporary Art in Kraków, presents the most recent contemporary art, both Polish and international. To be more precise, the Museum focuses on exhibiting contemporary art of the last two decades. It was opened quite recently—in 2011. Sport in Art was published to accompany an exhibition which took place between May and September 2012 in the Museum. It presents over forty artists and their unique perspectives and interpretations of sport. As Maria Anna Potocka stated, “The range and diversity of the artistic problems that arise under the influence of sporting inspiration are—even within the narrow scope of this exhibition—truly impressive.”